Arthroscopic‐guided ulnar distraction for the correction of elbow incongruency in four dogs. (23rd August 2013) - Coggeshall, J. D.; Reese, D. J.; Kim, S. E.; Pozzi, A.
<x xml:space="preserve">Abstract</x> Four skeletally immature, small breed dogs (five elbows) with elbow incongruency were evaluated for forelimb lameness. Findings on clinical examination included pain, effusion and decreased range of motion of the affected elbow. Radiography, computed tomography and arthroscopy demonstrated elbow incongruency in all dogs. Fragmented medial coronoid process was diagnosed arthroscopically in three dogs (four elbows). Arthroscopic subtotal coronoidectomy was performed in all cases of fragmented medial coronoid process. Incongruency was corrected with acute ulnar lengthening under arthroscopic visualisation. The ulna was stabilised with a plate following correction. In two elbows an ostectomy of the anconeal process was performed to prevent impingement against the olecranon fossa. All dogs demonstrated improvement in lameness scores and client‐scored visual analogue scale scores. Postoperative computed tomography showed significant improvement in elbow incongruency in all dogs. Arthroscopic‐guided ulnar lengthening may be considered as a valid treatment in severe cases of elbow incongruency.